2017
DOI: 10.20517/2574-1209.2016.04
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of buccal epithelium for genetic diagnosis of atherosclerosis using mtDNA mutations

Abstract: How to cite this article: Sinyov VV, Sazonova MA, Ryzhkova AI, Galitsyna EV, Melnichenko AA, Postnov AY, Orekhov AN, Grechko AV, Sobenin IA. Potential use of buccal epithelium for genetic diagnosis of atherosclerosis using mtDNA mutations. Vessel Plus 2017;1:145-50. Aim:The aim of this pilot study was to compare the heteroplasmy levels of specific mitochondrial (mt)DNA mutations in human buccal epithelial and whole blood cells in participants with different degrees of predisposition to atherosclerosis. The pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 13 publications
0
23
0
2
Order By: Relevance
“…Nevertheless, the results available to date position mitochondria as likely therapeutic targets for treatment of such diseases as cancer, chronic inflammatory states, and atherosclerosis. Selective mitochondria-targeting drugs, such as mitochondrial antioxidants, are being tested in preclinical and clinical trials [151,152]. Moreover, certain mtDNA mutations are being currently explored as diagnostic markers [152].…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the results available to date position mitochondria as likely therapeutic targets for treatment of such diseases as cancer, chronic inflammatory states, and atherosclerosis. Selective mitochondria-targeting drugs, such as mitochondrial antioxidants, are being tested in preclinical and clinical trials [151,152]. Moreover, certain mtDNA mutations are being currently explored as diagnostic markers [152].…”
Section: Future Directionsmentioning
confidence: 99%
“…Selective mitochondria-targeting drugs, such as mitochondrial antioxidants, are being tested in preclinical and clinical trials [151,152]. Moreover, certain mtDNA mutations are being currently explored as diagnostic markers [152]. Future studies will improve our understanding of the mechanisms of mitochondrial involvement in the pathological processes.…”
Section: Future Directionsmentioning
confidence: 99%
“…On the opposite, the latest findings on the role of mitochondrial DNA variation in individual predisposition to atherosclerosis provide a growing body of evidence and the expectation of the breakthrough in understanding of molecular mechanisms and pathways of atherogenesis [14,15] . Heteroplasmic mtDNA mutations represent a promising molecular biomarker of genetic susceptibility to atherosclerosis and related pathologies [16][17][18][19] . In our study, we have demonstrated that several atherosclerosis-associated mutations of mitochondrial DNA taken together as a mutation burden of mitochondrial genome possess their own explanatory power and give a significant increase atop of assessment of conventional risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction caused by mitochondrial DNA (mtDNA) damage is a well‐studied cause of cell dysfunction and death observed in atherosclerosis 7 . Correspondingly, dysfunctional mtDNA is regarded as a promising target for atherosclerosis treatment strategies.…”
Section: Introductionmentioning
confidence: 99%